PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN DAN LINGKUNGAN KELUARGA, TERHADAP MINAT INVESTASI MASYARAKAT GEN Z DI KABUPATEN BULELENG - Dwi Ferayani, Made (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to examine how Gen Z's interest in investing is influenced by family environment, financial behavior, and financial literacy. Gen Z students in Buleleng Regency served as the case study subjects. One hundred Gen Z students were given questionnaires to collect data, which were then analyzed using a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). According to the study's findings, investment interest is positively and significantly influenced by financial behavior, in turn by financial literacy, and by family environment. These results indicate that students' interest in investing increases with their level of financial knowledge, prudent financial behavior, and support from their family environment.